(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
In the early English Romantic literature, oriental themes began to flourish in the early XVIII century after the translation of the Arabian tales One Thousand and One Nights. The mysterious events, scenes, and character of the protagonists in these tales inspired many British writers to create works in a new genre called Oriental Tales, such as Byron and Thomas More. So this article is devoted to research the oriental features in the works of Byron and Thomas More.